Regulation of gonadotropins by corticotropin-releasing factor and urocortin - Kageyama, Kazunori (Frontiers in Endocrinology, 2013)
While stress activates the hypothalamic-pituitary-adrenal (HPA) axis, it suppresses the hypothalamic-pituitary-gonadal (HPG) axis. Corticotropin-releasing factor (CRF) is a major regulatory peptide in the HPA axis during stress. Urocortin1 (Ucn1), a member of the CRF family of peptides, has a variety of physiological functions and both CRF and Ucn1 contribute to the stress response via G protein-coupled seven transmembrane receptors. Ucn2 and Ucn3, which belong to a separate paralogous lineage from CRF, are highly selective for the CRF type 2 receptor (CRF2 receptor). The HPA and HPG axes interact with each other, and gonadal function and reproduction are suppressed in response to various stressors. In this review, we focus on the regulation of gonadotropins by CRF and Ucn2 in pituitary gonadotrophs and of gonadotropin-releasing hormone (GnRH) via CRF receptors in the hypothalamus. In corticotrophs, stress-induced increases in CRF stimulate Ucn2 production, which leads to the inhibition of gonadotropin secretion via the CRF2 receptor in the pituitary. GnRH in the hypothalamus is regulated by a variety of stress conditions. CRF is also involved in the suppression of the HPG axis, especially the GnRH pulse generator, via CRF receptors in the hypothalamus. Thus, complicated regulation of GnRH in the hypothalamus and gonadotropins in the pituitary via CRF receptors contributes to stress responses and adaptation of gonadal functions.